If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 4x + 3 = 0 Reorder the terms: 3 + 4x + 4x = 0 Combine like terms: 4x + 4x = 8x 3 + 8x = 0 Solving 3 + 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 8x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 8x = 0 + -3 8x = 0 + -3 Combine like terms: 0 + -3 = -3 8x = -3 Divide each side by '8'. x = -0.375 Simplifying x = -0.375
| 14-12=x/-4 | | 5x/4-3=7x/6 | | 17-3(4-3x)=6x-1 | | (-2z/y^3)^2 | | 1/3(m-3n)=2 | | 3x(-5)/2x | | 0.55=logx | | -4-p=8p-5(6+7p) | | (3xy^2-2y)=0 | | f(2e^4)=lnx | | 2=4-2f | | 81/54 | | 10x-20=-5x+10 | | -15=-k-4k | | x-.15x=7849.08 | | 4a^2-6a^6/8a^-3 | | x+6+3x=-18 | | 6-14=z/-4 | | 30+.5x=1.25x | | x+(-7)=-77 | | x-.15x=4812.96 | | 4.25z=4.5z-6.25+6.25 | | x^2+4x+8y+1=0 | | x^2+10x+y+20=0 | | -3b+9=15 | | -3k-4-1=7 | | -3b+9= | | 12(x-2)+15=4x-23 | | 7+2(x-3)=5 | | t/9-3 | | 3X^2-50-282=0 | | 0.3x+20=2x+20 |